2016
DOI: 10.1111/hae.12903
|View full text |Cite
|
Sign up to set email alerts
|

Type 2M von Willebrand disease – more often misidentified than correctly identified

Abstract: Type 2M VWD is more often misidentified (70.6%) than correctly identified as 2M VWD (29.4%), and potentially explaining the relative under-reported incidence of 2M VWD in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 39 publications
2
62
0
Order By: Relevance
“…Unfortunately, laboratory testing for VWD is imperfect, and all phenotypic tests are subject to error, as is multimer analysis. For example, a background error rate of~10% can be associated with phenotypic testing, although error rates for specific VWD types can be higher or lower [7,8]. 2M VWD in particular is more often misdiagnosed as Type 1 or 2A VWD than correctly diagnosed as 2M [6,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, laboratory testing for VWD is imperfect, and all phenotypic tests are subject to error, as is multimer analysis. For example, a background error rate of~10% can be associated with phenotypic testing, although error rates for specific VWD types can be higher or lower [7,8]. 2M VWD in particular is more often misdiagnosed as Type 1 or 2A VWD than correctly diagnosed as 2M [6,8].…”
mentioning
confidence: 99%
“…For example, a background error rate of~10% can be associated with phenotypic testing, although error rates for specific VWD types can be higher or lower [7,8]. 2M VWD in particular is more often misdiagnosed as Type 1 or 2A VWD than correctly diagnosed as 2M [6,8]. Most errors can be linked to analytical issues or postanalytical (mis)interpretation of test findings.…”
mentioning
confidence: 99%
“…This condition is also seen in VWD patients lacking in large multimers, that is, in those with type 2A or type 3 or severe type 1, with VWF levels below 10 U/dL. 26,27 Since all the type 2M VWD patients described to date have had normal or only slightly reduced VWF levels, the combination of a defective or absent RIPA with normal or near normal VWF levels can point to both type 2M or type 2A…”
Section: Discussionmentioning
confidence: 99%
“…This assay which is interpreted in a similar fashion, but remains under‐recognized, is not frequently used in routine practice as the ELISA (enzyme‐linked immunosorbent assay) method has not been fully automated. However, Favaloro et al identified that the 3 “standard” test panels (FVIII, VWF:Ag, VWF:RCo) must be optimized by VWF:CB assay to reduce misdiagnosis of VWD . In particular, diagnosis of type 2M VWD was missed by 75‐90% of laboratories using only 1 of the 2 VWF activity assays (VWF:RCo or VWF:CB), whereas the error rate was 3 times lower in the laboratories performing the 2 activity assays …”
Section: Introductionmentioning
confidence: 99%
“…However, Favaloro et al identified that the 3 "standard" test panels (FVIII, VWF:Ag, VWF:RCo) must be optimized by VWF:CB assay to reduce misdiagnosis of VWD. [8][9][10] In particular, diagnosis of type 2M VWD was missed by 75-90% of laboratories using only 1 of the 2 VWF activity assays (VWF:RCo or VWF:CB), whereas the error rate was 3 times lower in the laboratories performing the 2 activity assays. 8 Recently, a chemiluminescent method (HemosIL AcuStar VWF:CB; Instrumentation Laboratory, Bedford, MA, USA) has been commercialized.…”
Section: Introductionmentioning
confidence: 99%